Block hybrid-like method for solving delay differential equations - Yap, Lee Ken; Ismail, Fudziah (AIP Publishing LLC, 2014)
The block hybrid-like method is presented and implemented in predictor-corrector mode to solve delay differential equations. The Lagrange interpolation polynomial is implemented to obtain the approximation for the delay terms. The Q-stability of the method is investigated. The illustrative examples are presented to demonstrate the efficiency of the block hybrid-like method.